2014
DOI: 10.1002/lary.25094
|View full text |Cite
|
Sign up to set email alerts
|

Lateral neck recurrence from papillary thyroid carcinoma: Predictive factors and prognostic significance

Abstract: 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 22 publications
(59 reference statements)
0
18
0
Order By: Relevance
“…Lateral LNs metastases are considered as a more advanced stage of PTC, with a relatively high incidence of recurrence and early postoperative morbidity . Although the LND incision length was decreased, a neck scar is still unavoidable after conventional surgery, which is of great concern to young women and people with particular occupations for patients who insist that cosmetic appearance is of great importance.…”
Section: Discussionmentioning
confidence: 99%
“…Lateral LNs metastases are considered as a more advanced stage of PTC, with a relatively high incidence of recurrence and early postoperative morbidity . Although the LND incision length was decreased, a neck scar is still unavoidable after conventional surgery, which is of great concern to young women and people with particular occupations for patients who insist that cosmetic appearance is of great importance.…”
Section: Discussionmentioning
confidence: 99%
“…However, the clinical behaviors of this cancer are complex and varied. Cervical lymph node metastasis (LNM) is frequently observed in PTC patients with an average incidence of 60% 1 because PTC tends to spread via lymphatic ducts 2 . According to some studies, PTC LNM are reported to have no significantly clinical effects on the outcomes in low-risk patients, however, a study with large samples (9904 patients) found that PTC with LNM, age >45 years, distant metastasis, and large tumor size could significantly predict poor overall survival outcome 3 .…”
Section: Introductionmentioning
confidence: 99%
“…However, the clinical behaviors of this cancer are complex and varied. PTC is easy to spread via lymphatic ducts, which results in recurrence, metastases, and even death [ 1 ]. Recurrent PTC mainly refers to localized and distant recurrence, including recurrence of the primary tumor, lymph node metastases, invasion of the esophagus and trachea, invasion of muscles, soft tissues and nerves, and distant metastases.…”
Section: Introductionmentioning
confidence: 99%